2008
DOI: 10.1111/j.1471-0307.2008.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of some properties of banana yogurts made with commercial ABT‐2 starter culture during storage

Abstract: Five yogurt batches were prepared with banana puree and sugar combinations and ABT-2 (Streptococcus salivarius ssp. thermophilus, Lactobaccilus acidophilus and Bifidobacterium spp.) as starter culture. The addition of fruit influenced (P < 0.05) the syneresis, titratable acidity and pH, whereas the viscosity value, and S. salivarius ssp. thermophilus, L. acidophilus and Bifidobacterium spp. counts were found to be insignificant. Storage time significantly (P < 0.05) affected the syneresis, titratable acidity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
19
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 41 publications
21
19
0
1
Order By: Relevance
“…Soluble solids were significant different between formulas, and as expected the yogurt control had the lowest value since no solids were added as gum or caramel jam. Bakirci and Kavaz (2008) added banana puree to yogurt and obtained solid contents between 10.3 and 19.0 g/100 g, consistent with those of this study.…”
Section: Physicochemical Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…Soluble solids were significant different between formulas, and as expected the yogurt control had the lowest value since no solids were added as gum or caramel jam. Bakirci and Kavaz (2008) added banana puree to yogurt and obtained solid contents between 10.3 and 19.0 g/100 g, consistent with those of this study.…”
Section: Physicochemical Analysissupporting
confidence: 92%
“…pH values did not differ significantly, within formulas; while the control had the lowest pH. These values are similar to pH values reported by Aportela-Palacios, Sosa-Morales, and Vélez-Ruiz (2005), for yogurt added with fiber and calcium ranging of 4.5 to 4.2; and similar to a study of Bakirci and Kavaz (2008) for banana yogurts. Furthermore, Celik et al (2006) found in yogurt flavored with cherry paste, values of acidity that varied between 0.80 and 0.93 g, while Soukolis et al (2007) studied industrial yogurts with acidity values of 0.90 ge0.95 g of lactic acid in 100 mL, higher than those obtained in this study, probably due to the addition of acidic fruits for the first case, and a longer fermentation process for the second one.…”
Section: Physicochemical Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…El yogurt por su presencia en el mercado internacional y su elevado consumo, es el producto lácteo fermentado más importante a nivel industrial (Özer y Kimarci, 2010;Bakirci y Kavaz, 2008). Los desarrollos metodológicos sobre la elaboración del yogurt han sido llevados a cabo principalmente siguiendo el proceso tradicional sobre la leche de vaca, incluyendo: estandarización, pasteurización a 90°C por 10-30 min, homogeneización y enfriamiento a 45 -47°C, inoculación con el cultivo iniciador, incubación a 40°C, rápido enfriamiento a 4-7°C y empacado final (Tamime y Robinson, 2000).…”
Section: Introductionunclassified